التنظيم الذاتي في وسائل الاعلام الجزائرية-دراسة ميدانية - بركاتي, عبد النور (University of Eloued جامعة الوادي, 2022)
تهدف الدراسة إلى معرفة ادوار وقيم وجود و غياب آليات التنظيم الذاتي ضمن عمل وسائل الإعلام الجزائرية، لما تشكله من ضابط مهم للضمير المهني في وسائل الإعلام التقليدية والالكترونية،وتختلف أدوات التنظيم في وجودها من وسيلة إلى أخرى من مواثيق شرف أو مدونات سلوك أو مذكرات مصلحيه توجيهية، وكل لها درجة القوة في الفرض والتأثير وتوجيه مسار العمل الصحفي لدى الصحفيين والقائمين بالاتصال، في ظل بروز مظاهر عمل غير مهنية وأخلاقية كانتهاك حرمة الحياة الخاصة وغيرها من المحاذير الصحفية، ما تطلب وجود هذه الآليات الداخلية خاصة داخل المؤسسات وأجسام إعلامية عامة تكون الرقيب المهني لوسائل الإعلام المختلفة. The study aims to know the roles and values of the presence and absence of self-regulation mechanisms within the work of the Algerian media, as it constitutes an important control of the professional conscience in the traditional and electronic media. All have a degree of strength in imposing, influencing and directing the course of journalistic work for journalists and communicators, in light of the emergence of unprofessional and ethical work manifestations such as violating the sanctity of private life and other journalistic warnings, which require the existence of these internal mechanisms, especially within institutions and public media bodies that act as the professional watchdog for the media. different media.